Accelerating the transformation of the rice sector in Burkina Faso: moving from technology to system-wide pathways - Kpadonou, G Esaie; Ganyo, Komla Kyky; Segnon, Alcade Christel; Dossou Yovo, Elliot R; Dicko, Mohamed; Sall, Abdou; Batieno, Benoit Joseph; Ndaw, Omar; Ouattara, Yabile Florence; Kane, Mahamadi; Lamien, Nieyidouba; Zougmore, Robert Bellarmin (2025)
The transformation of the rice sector in West Africa remains a strategic priority as rising consumption continues to outpace regional production, leading to persistent reliance on imports exceeding 15 million tons annually. Despite years of investments aimed at closing the yield gap, the rice sector has not undergone the structural transformation needed to achieve competitiveness, reduce climate and market vulnerability, and generate broader economic opportunities. In this context, AICCRA-led side event during the 2025 FRSIT (Forum national de la recherche scientifique et des innovations technologiques) in Ouagadougou, Burkina Faso provided an important platform to examine the state of technologies and innovations (T&Is), stakeholder needs, and systemic barriers within the rice value chain in Burkina Faso. Using an embedded single-case study design, this report draws on three integrated data streams: (i) an inventory of 44 rice-related technologies, (ii) participant profiling (n = 290), and (iii) multiple sources of qualitative discourse, to analyze the alignment between technology supply, user demand, and the institutional environment. The analysis reveals a strong technological concentration on the production stage (65% of T&Is), contrasting with major stakeholder concerns around post-harvest losses, processing capacity, market access, financing, and regulatory inconsistencies. Survey data confirm low awareness of existing climate-smart technologies, particularly climate-resilient varieties and digital advisory tools. Consequently, scaling of existing CSA technologies needs to be more prioritized. Stakeholders identified four major drivers for accelerating industrialization in rice sector: (i) tailored financing mechanisms; (ii) strengthened capacity building and extension systems; (iii) renewed investment in research and development; and (iv) stronger public–private partnerships. Overall, findings highlight the necessity of shifting from a production-centric innovation agenda to a systemic transformation approach that simultaneously addresses technological readiness, market structure, governance, and institutional coordination across the value chain.